Coptotermes gestroi (Isoptera, Rhinotermitidae): dinâmica de colônias inteiras, necessidades hídricas e alocação de castas entre diferentes fontes alimentares - Janei, Vanelize [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
optotermes gestroi is an Asian subterranean termite introduced in Brazil, responsible for severe economic damages in urban areas. As the management of a pest is only efficient with the knowledge of its biology, the behavior study of complete laboratory colonies contributes to future orientations in prevention and management of this pest termite species. Laboratory colonies are an unique study opportunity, because they allow long term monitoring, and also give an idea of what occurs with these insects in nature. In view of that, the main objective of this study was to understand the behavior dynamics of complete colonies of C. gestroi through bioessays, and for that were used 3 to 7 years old colonies of C. gestroi from the termite laboratory of UNESP Rio Claro. Experiments with these colonies allowed understanding the allocation of brood and reproductives movement between the different food sources in a colony, as well as water requirements of foraging groups and of the complete colony. The study reported in chapter 1 with 3 years old colonies aimed to understand how the exploration of a new food source occurs in complete colonies, taking under consideration the time spent by termites to discover the new source and the number of individuals in the traffic between two recipients. In chapter 2 the data of population census of colonies kept for 6, 9 and 12 months in laboratory are ordered. The study of the chapter 3 reports three types of experiments with 4, 5 and 6 years old colonies and aimed to clarify the transference and moviment of the reproductive caste, besides the transport of larva and eggs, to other similar or different food sources. Chapter 4 presents data of experiments with 7 years old complete colonies and intended to evaluate what are the water requirements of these colonies considering the time it took them to find water sources and individuals traffic to these sources. Additionally, this chapter also reports experiments to...

Coptotermes gestroi é um cupim subterrâneo asiático introduzido no Brasil, responsável por severos danos econômicos em áreas urbanas. Como o manejo de uma praga só é eficiente com o conhecimento de sua biologia, o estudo do comportamento de colônias inteiras contribui para orientações futuras na prevenção e manejo desta espécie de cupim praga. Colônias de laboratório proporcionam uma oportunidade única de estudo, pois permitem um monitoramento a longo prazo, além de proporcionar uma ideia do que ocorre com estes insetos na natureza. Em vista do exposto, o objetivo principal deste estudo foi entender a dinâmica comportamental de colônias inteiras de C. gestroi por meio de bioensaios e, para isso, foram utilizadas colônias de C. gestroi de 3 a 7 anos de idade provenientes do laboratório de cupins da UNESP de Rio Claro. Experimentos com estas colônias permitiram entender a alocação de jovens e o movimento de reprodutores entre as diferentes fontes alimentares de uma colônia, bem como as necessidades hídricas de grupos de forrageiros e da colônia como um todo. O estudo relatado no capítulo 1 com colônias de 3 anos foi realizado para tentar compreender como ocorre, em colônias inteiras, a exploração de uma nova fonte alimentar, levando em consideração o tempo que os cupins levaram para descobrir a nova fonte e o número de indivíduos nos fluxos de um recipiente para outro. No capítulo 2 estão dispostos os dados relativos ao censo das populações das colônias mantidas por 6, 9 e 12 meses no laboratório. O estudo do capítulo 3 relata três tipos de experimentos realizados com colônias de 4, 5 e 6 anos e visou elucidar a transferência e o deslocamento da casta reprodutora, além do transporte de larvas e ovos, para outras fontes alimentares iguais ou diferentes. O capítulo 4 apresenta os dados de experimentos com colônias inteiras de 7 anos e pretendeu avaliar quais as necessidades hídricas destas colônias...
Keywords: Termites; Térmita; Casta; Comportamento social dos animais; Sociedades de insetos; Animais - Comportamento; Animais - Alimentos